Histopathological Findings in an Unclassifiable Case of Empty Nose Syndrome with Long-term Follow-up - Dzhenkov, Deyan L (Cureus, 2018)
One of the major components of the functional process in the nasal cavity is taken up by the respiratory epithelium covering the posterior two-thirds of the nasal cavity. Disruption in the cytoarchitectonics and subcellular changes in this epithelium results in a number of functional changes in the nasal cavity. One of the rare and usually iatrogenic disturbances of this type is described in 1996, although noticed and discussed significantly earlier, by Kern and Stenkvist empty nose syndrome (ENS) or secondary atrophic rhinitis. The clinical hallmarks of ENS are described as paradoxical feeling for nasal obstruction in the presence of actually widened nasal airways. This phenomenon is attributed to the efferent neuronal signal dissociation accompanying the changes in the nasal mucosa. Herein we report the findings in a 50-year-old male. The patient presented with chronic right-sided headache, foul discharge and complaints of a stuffed nose in 2011. Endoscopy and computed tomography (CT) showed complete destruction of the hard plane, nasal septum, and right maxillary septum, leading to a formation of a huge neocavity. Due to the past medical history and the severity of the case biopsy specimens were obtained under general anesthesia. The sections showed severe but unspecific changes of the nasal epithelium with areas of minimal remaining preserved respiratory epithelium. Based on the clinical data and endoscopic, CT and histomorphologic data, despite the case is not applicable to the current classification of ENS, the diagnosis of ENS was accepted based on the combined extensive but unspecific findings. A seven-year follow-up period included multiple hospital admissions for monitoring of the condition and extensive sinus lavage. No advancement was noticed.